A Review On Gamma-Aminobutyric Acid (Gaba) And Its Receptors - M.SUDHEER KUMAR; I. J. KUPPAST (International Journal of Pharma and Bio Sciences, 2012)
The inhibitory neurotransmitter, γ-aminobutyric acid (GABA), activates a variety of receptors in all areas of the central nervous system (CNS). GABA acts at inhibitory synapses in the brain by binding to specific transmembrane receptors in the plasma membrane of both pre and postsynaptic neuronal processes. There are three classes of GABA receptors. GABAA and GABAC receptors are ionotropic in nature (i.e., their activation results in enhanced membrane ion conductance) and GABAB receptor is metabotropic type of receptor (i.e., their activation results in increased intracellular levels of second messenger). GABA is present in high concentrations (millimolar) in many brain regions. The GABAA receptor is a complex structure and includes the five major binding domains. These include binding sites localized in or near the Cl− channel for GABA, benzodiazepines, barbiturates and picrotoxin as well as binding sites for the anesthetic steroids. GABAB receptors (GABAB) are metabotropic transmembrane receptors for gamma-aminobutyric acid (GABA) that are linked via G-proteins to potassium channels. These GABAB receptors are activated by baclofen. In addition to the GABAB receptors there is a distinct class of ligand gated ion channels that are activated by GABA, referred to as the GABAC receptor. The GABAC receptors are activated by cis-aminocrotonic acid (CACA), which is not recognised by either the GABAA or GABAB receptors. GABAC receptors are expected to mediate the lateral inhibition of light responses and have been shown to inhibit transmitter release at bipolar cell terminals. The pharmacology of these novel subtypes of GABA receptors may yield important therapeutic agents.